Invasive mechanical ventilation weaning checklist and extubation in adult cardiac patients: an integrative review (Research, Society and Development, 2023)
Objective: To identify, through a review, the existence of checklists for weaning and extubation in patients with heart disease. Method: This is an integrative literature review with a descriptive and qualitative approach, which was carried out through the survey of scientific articles that were related to the objective of the study. A survey was carried out in the databases of the National Library of Medicine (PubMed); Scopus; PEDro; and Lilacs. Inclusion criteria were articles that related to the proposed theme, published in the last 10 years, available in full and without language restriction. The exclusion criteria were bibliographic review articles, articles or abstracts published in conference proceedings, monographs and theses; letters from editors and preprints. Results: 189 articles were found, the titles and abstracts were screened, after that, 186 articles were excluded for not meeting the eligibility criteria, leaving 3 articles that were carefully read in full, after complete reading, 2 articles were selected. Final considerations: Several factors can interfere with the weaning process and its success, in addition to positive results after extubation. The most important is that the absence of weaning protocols increases the number of unscheduled extubations. Research with greater methodological rigor and the application of specific tools is necessary for this group that suffers from several clinical interferences in its successful weaning and extubation.